The Relationship between Social Skills and Academic Achievement of Universitas Klabat Students - Simanungkalit, Ate Gueen L. R. (11th International Scholars Conference, 2017)
This descriptive quantitative study was intended to explore the association between social skills and academic achievement and comparison based on gender. The respondents were 139 students who took a general requirement course, namely Philosophy of Christian Education as offered in Universitas Klabat Indonesia. The respondents’ participation was made on voluntary basis. The questionnaire Social Skill Rating System originally developed by Gresham and Elliot (1990) was used as the instrument to get the data. Being translated, the 39-item questionnaire underwent tests of validity and reliability. The findings indicated that overall the students had high level of social skills and their academic achievement in terms of their average score of course grade was considered excellent. For social skills in terms of gender, there was no significant difference even though female is higher than male on both variables. But for academic achievement based on gender, there was a significant difference, wherein the female students showed significantly higher score than that of male students. The social skills were not found to be significantly associated with academic achievement. However, it did not mean that social skills did not work. It could also mean that the student might not need social skills for developing their academic achievement.